Romeo and Juliet - Shakespeare, William, 1564-1616.; Costa, Jana (London : Usborne, 2006)
Developed in conjunction with experts from the University of Surrey, this work is designed to encourage independent reading. Accompanied by illustrations, it is a part of the "Usborne Young Reading Series", which re-examines the tragedy of William Shakespeare's "Romeo and Juliet".
3-6.